How and when fungal endophytes can eliminate the plant growth–defence trade-off: mechanistic perspectives - Bastías, Daniel A. (2022)
A central paradigm in plant biology is that there is a trade-off between growth and defence against biotic stresses (Herms & Mattson, 1992; Lind et al., 2013; Karasov et al., 2017; Zust & € Agrawal, 2017; Monson et al., 2022). This paradigm is based on recurrent observations that increased production of chemical defences is associated with compromised plant growth, and it provides obvious limits to increasing the productivity of plants that must also resist pests and pathogens (Ballare & Austin, 2019; Ha et al., 2021; Sestari & Campos, 2021).We have recently challenged this paradigm by proposing that fungal endophytes can simultaneously increase plant growth and defence against biotic stresses (Fig. 1) (Bastıas et al., 2021).